2017
DOI: 10.1007/s40572-017-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Assessing Long-Term Exposures to Outdoor Air Pollutants

Abstract: Purpose of ReviewEpidemiological studies of health effects of long-term exposure to outdoor air pollution rely on different exposure assessment methods. This review discusses widely used methods with a special focus on new developments.Recent FindingsNew data and study designs have been applied, including satellite measurements of fine particles and nitrogen dioxide (NO2). The methods to apply satellite data for epidemiological studies are improving rapidly and have already contributed significantly to nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
108
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 106 publications
0
108
0
Order By: Relevance
“…Therefore, when considering the housing type of Koreans, changes in PM 2.5 concentrations based on height can be an important issue. Although PM 2.5 concentrations differ depending on the height of the apartment, matching the estimated values at ground level can cause the overestimation of ambient PM 2.5 exposures in epidemiological studies 12. Third, the exposure-risk function used in this study was obtained from the result of cohort studies conducted in North America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when considering the housing type of Koreans, changes in PM 2.5 concentrations based on height can be an important issue. Although PM 2.5 concentrations differ depending on the height of the apartment, matching the estimated values at ground level can cause the overestimation of ambient PM 2.5 exposures in epidemiological studies 12. Third, the exposure-risk function used in this study was obtained from the result of cohort studies conducted in North America.…”
Section: Discussionmentioning
confidence: 99%
“…The CRAs for each disease caused by PM 2.5 are mainly derived from long-term cohort studies, and these results are used to calculate the population attributable fraction (PAF) of PM 2.5 for each disease 11. Because measurement of PM 2.5 concentrations has not been long worldwide, assessment of long-term exposure in epidemiological studies related to PM 2.5 exposure has been challenging 12. In the past, PM 2.5 exposure has been measured in several cities using routine ground monitoring, and health effects due to long-term exposures have been estimated in cohort studies 1314.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned hypothesis is reinforced by several previous studies. As reported by Hoek, the spatial stability of air pollution contrasts is a necessary assumption for application of recently developed models for long-term exposure [50]. The same author observed that, for traffic-related pollutants including PM, spatial stability can be expected [50].…”
Section: Discussionmentioning
confidence: 89%
“…As reported by Hoek, the spatial stability of air pollution contrasts is a necessary assumption for application of recently developed models for long-term exposure [50]. The same author observed that, for traffic-related pollutants including PM, spatial stability can be expected [50]. Moreover, the assumption that within-city spatial patterns remain constant over the years, also when mean concentrations of air pollutants change over time, has been made within the European Study of Cohorts for Air Pollution Effects (ESCAPE) [51].…”
Section: Discussionmentioning
confidence: 99%
“…(2) lack of the assessment of the indoor air quality [4,5], as most of the models dismiss the difference between the indoor/outdoor pollution and essentially use the outdoor air pollution as a proxy for overall exposure [6,7]; (3) static spatio-temporal approach to the exposure assessment based mostly on residential address and without taking into consideration individuals' mobility throughout the day [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%